1998
DOI: 10.1136/gut.43.3.322
|View full text |Cite
|
Sign up to set email alerts
|

The relation between gastric vitamin C concentrations, mucosal histology, and CagA seropositivity in the human stomach

Abstract: Background-Vitamin C may be protective against gastric cancer though infection with Helicobacter pylori is associated with a reduction in intragastric concentrations of vitamin C. Aims-To examine the eVects of H pylori infection, gastric juice pH, the severity and extent of gastric inflammation, and CagA antibody status of the individual on gastric juice and mucosal vitamin C concentrations. Patients-One hundred and fifteen patients undergoing routine gastroscopy for investigation of dyspepsia. Methods-High pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 29 publications
4
108
0
2
Order By: Relevance
“…Increased cell proliferation in the absence of a corresponding increase in apoptosis may explain the increased gastric cancer risk associated with infection by CagA + strains [10] . protein is carcinogenic, the enhanced inflammation and marked reduction of gastric juice vitamin C levels in CagA + strain infected patients may ply a role in H. pylori associated carcinogenesis [16] . H. pylori expresses a powerful urease enzyme, which catalyses the conversion of urea to ammonia.…”
Section: Bacterial Virulence Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased cell proliferation in the absence of a corresponding increase in apoptosis may explain the increased gastric cancer risk associated with infection by CagA + strains [10] . protein is carcinogenic, the enhanced inflammation and marked reduction of gastric juice vitamin C levels in CagA + strain infected patients may ply a role in H. pylori associated carcinogenesis [16] . H. pylori expresses a powerful urease enzyme, which catalyses the conversion of urea to ammonia.…”
Section: Bacterial Virulence Factorsmentioning
confidence: 99%
“…A series of studies have demonstrated that concentrations of ammonia comparable to those found in gastric juice of infected individuals can cause gastric atrophy in rats, increase epithelial cell proliferation, and act as a promoter in the methyl-N' nitro-Nnitrosoguanidine (MNNG) rat model of gastric cancer [23][24][25][26][27][28] . Furthermore, H. pylori phospholipases, proteases and oxidases have been shown to cause degradation of many molecules, such as phospholipids in bio-membranes, transforming growth factor-β (TGF-β) and vitamin C, which are important in preventing carcinogenesis [16,[29][30][31] .…”
Section: Bacterial Virulence Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since H. pylori was discovered (Warren and Marshall 1983) and its pathogenesis was reported (Marshall et al 1985), many researchers have taken notice of various factors associated with the development of this disease, especially carcinogenesis, and have conducted many biological studies (Anti et al 1998;Honda et al 1998;Sugiyama et al 1998;Watanabe et al 1998;Zhang et al 1998;El-Omar et al 2000;Peek et al 2000;Wang et al 2000). At the same time, many epidemiological studies have been published in the international literature.…”
Section: Helicobacter (H) Pylorimentioning
confidence: 99%
“…This is deduced from the results that nitrous acid-induced oxidation of quercetin and chlorogenic acid is inhibited by ascorbic acid [37,38] and the inhibition accompanies the formation of monodehysroascorbic acid radical [38]. The ascorbic acid-dependent inhibition of their oxidation suggests that ascorbic acid in gastric juice, the concentration of which ranges from 0 to 0.5 mM (average, about 0.1 mM) [39][40][41], can suppress the nitrous acid-induced oxidation of phenolic compounds in the stomach. These results suggest that efficiency of the transport of phenolic compounds, which can react with nitrous acid readily, to the intestine is dependent on the concentrations of both salivary nitrite and gastric ascorbic acid.…”
Section: Nitric Oxide ( • No) Formationmentioning
confidence: 99%